IMPROVING STUDENT’S READING COMPREHENSION THROUGH ENGLISH SHORT STORY AT ELEVENTH GRADE OF SMAS NU CENTINI LAREN LAMONGAN - Zanuba Arifah Khofshoh; Moch. Arifin (PROJECT (Professional Journal of English Education), 2021)
The focus of this teaching and learning activity is to improve students' reading comprehension through English short stories in eleventh grade students of SMAS NU Centini Laren Lamongan. Utilizing the existence of English short stories as a medium is expected to make a positive contribution to students through their characteristics that make readers feel happy. This research is a Classroom Action Research which is carried out by following John Elliot's model research procedures which include planning, action, observation, reflection or evaluation. The research was carried out in the eleventh class of SMAS NU Centini Laren Lamongan for the academic year 2019-2020 even semester totaling 50 students. The results showed that before being given learning using short story books in English, the average value of reading comprehension was 56 (8%) in the very low category. After learning reading comprehension was carried out using English short story book media in the first cycle the average value of students 'reading comprehension increased to 67 (38%), still in the moderate category, and learning was carried out in the second cycle the students' reading comprehension ability increased the average score. and a percentage of 77 (86%) with a very high category. By using this method, there was a fairly good increase for the students of SMAS NU Centini Laren Lamongan. In addition, other results obtained were students easier to absorb and understand English learning material and this activity was also the starting point for other activities. Keywords:  Reading Comprehension, Short Story, CAR